Microwave ablation induces abscopal effect via enhanced systemic antitumor immunity in colorectal cancer - Yu, Lu; Xie, Hairong; Wang, Linping; Cheng, Min; Liu, Jie; Xu, Jiamei; Wei, Zhigang; Ye, Xin; Xie, Qi; Liang, Jing (Frontiers in Oncology, 2023)
Background Thermal ablation is the primary procedure for the local treatment of lung metastases. It is known that radiotherapy and cryoablation can stimulate an abscopal effect, while the occurrence of abscopal effect induced by microwave ablation is less; the cellular and molecular mechanisms involved in the abscopal effect after microwave ablation should be further elucidated. Methods CT26 tumor-bearing Balb/c mice were treated with microwave ablation with several combinations of ablation power and time duration. The growth of primary or abscopal tumors and the survival of mice were both monitored; moreover, immune profiles in abscopal tumors, spleens, and lymph nodes were examined by flow cytometry. Results Microwave ablation suppressed tumor growth in both primary and abscopal tumors. Both local and systemic T-cell responses were induced by microwave ablation. Furthermore, the mice exhibiting significant abscopal effect after microwave ablation markedly elevated Th1 cell proportion both in the abscopal tumors and spleens. Conclusions Microwave ablation at 3 w–3 min not only suppressed tumor growth in the primary tumors but also stimulated an abscopal effect in the CT26-bearing mice via the improvement of systemic and intratumoral antitumor immunity.